1999
DOI: 10.1161/01.hyp.34.4.987
|View full text |Cite
|
Sign up to set email alerts
|

Statins and Blockers of the Renin-Angiotensin System

Abstract: Abstract-In addition to their primary mode of action, statins and blockers of the renin-angiotensin system possess common additional properties that are under active investigation. The inhibition of cellular proliferation, the restoration of endothelial activity, the inhibition of platelet reactivity, and an antioxidant potential are only a few examples of shared effects that target the arterial wall. These and other properties may eventually become exploited for the improved treatment of cardiovascular diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(30 citation statements)
references
References 95 publications
3
25
0
2
Order By: Relevance
“…Our speculations regarding intracellular mechanisms also require further testing. However, the data we report here and those from other studies (32,33) support the concept that statins have novel pleiotropic effects on intracellular signaling, independent of circulating cholesterol levels.…”
Section: Discussionsupporting
confidence: 84%
“…Our speculations regarding intracellular mechanisms also require further testing. However, the data we report here and those from other studies (32,33) support the concept that statins have novel pleiotropic effects on intracellular signaling, independent of circulating cholesterol levels.…”
Section: Discussionsupporting
confidence: 84%
“…Data from the same cohort of patients suggested that this improvement was due to reduced arterial wall stiffness caused by ACE-inhibitors in the treatment group (Ahimastos et al, 2008). Like Statins, ACE-inhibitors have pleiotropic vascular protective effects including plaque stabilisation, improved vasomotor dysfunction and many biochemical mechanisms including inhibition of platelet adhesion and aggregation, inhibition of platelet derived growth factor, endothelin, and stimulation of endothelial relaxation via stimulation of nitric oxide and prostacyclin (Faggiotto and Paoletti, 1999).…”
Section: Antihypertensive Therapymentioning
confidence: 99%
“…While the risk for stroke was unaffected, the hazard ratio for transient ischemic attacks was 0.75 in the treatment group compared to placebo. As well as improving overall survival, statins improve symptoms of PAD through pleiotropic effects, thought to be mediated through a reduction in endothelial dysfunction, plaque stabilisation and anti-inflammatory effects (Kinlay, 2005, Faggiotto andPaoletti, 1999). The Scandinavian Simvastatin Survival Study found a 38% decrease in "new or worsening claudication" over a 5.4 yr period in 4,444 patients treated with simvastatin (1994c).…”
Section: Lipid Lowering Therapymentioning
confidence: 99%
“…Por la reducción de la incidencia de infarto de miocardio y muerte cardiaca observada en ensayos clínicos sobre IECA en la insuficiencia cardiaca y tras infarto de miocardio, se ha investigado su utilidad para la prevención secundaria en pacientes con enfermedad coronaria sin insuficiencia cardiaca [170][171][172][173][174] . En los estudios HOPE y EUROPA la reducción relativa del riesgo de los objetivos primarios se situaba en el orden del 20%, mientras que en el estudio PEACE no se observó una reducción significativa con el uso de IECA.…”
Section: Inhibidores De La Enzima De Conversión De Angiotensinaunclassified
“…Los efectos del ramipril y el perindopril en la reducción de la presión arterial, comparados con placebo, también pueden haber influido en la reducción del riesgo en los estudios HOPE y EUROPA, aunque los IECA podrían aportar una cardioprotección adicional 172 . Además, los IECA son un tratamiento bien establecido en la insuficiencia cardiaca y en la disfunción del VI 173 y en pacientes diabéticos 136 .…”
Section: Inhibidores De La Enzima De Conversión De Angiotensinaunclassified